(untitled) (Open Herald: Periodical of Methodical Research, 2024)
The article discusses the current issues of achieving educational efficiency in the conditions of new Uzbekistan. Also, the advantages of using innovative methods in the formation of students’ communicative competence characteristics, the content of using innovative methods are highlighted